Design of a bolting robot for constructing steel structure - Nam, H.; Choi, W.; Ryu, D.; Lee, Y.; Lee, S.-H.; Ryu, B. (ICCAS 2007 - International Conference on Control, Automation and Systems, 2007)
During the last two decades, the automation for constructing a steel structure has been extensively studied. However, the bolting process is still remained as a manual work, and the human workers climbs the vertical steel beams on top of the high-rise steel structure in many construction fields. The manual bolting process is extremely dangerous and inefficient. To resolve this problem, a new bolting robot is developed in this research. The bolting robot composed of two parts, a posturing base and bolting grippers. The posturing base is specially designed to ensure the convenient posture to approach the bolting holes. The bolting gripper equips a bolting tool, and fastens the bolt with respect to a predefined torque. Some experiments ware conducted to evaluate the developed system, and it successfully carried out the automated bolting process. ？ ICROS.